The Brisbane Declaration and Global Action Agenda on Environmental Flows (2018) - Arthington, Angela H.; Bhaduri, Anik; Bunn, Stuart E.; Jackson, Sue E.; Tharme, Rebecca E.; Tickner, Dave; Young, Bill; Acreman, Mike; Baker, Natalie; Capon, Samantha; Horne, Avril C.; Kendy, Eloise; et al. (Frontiers in Environmental Science, 2018)
A decade ago, scientists and practitioners working in environmental water management crystallised the progress and direction of environmental flows science, practice and policy in The Brisbane Declaration and Global Action Agenda (2007), during the 10th International Riversymposium and International Environmental Flows Conference held in Brisbane, Australia. The 2007 Declaration highlights the significance of environmental water allocations for humans and freshwater-dependent ecosystems, and sets out a nine-point global action agenda. This was the first consensus document that bought together the diverse experiences across regions and disciplines, and was significant in setting a common vision and direction for environmental flows internationally. After a decade of uptake and innovation in environmental flows, the 2007 declaration and action agenda was revisited at the 20th International Riversymposium and Environmental Flows Conference, held in Brisbane, Australia, in 2017. The objective was to publicize achievements since 2007 and update the declaration and action agenda to reflect collective progress, innovation, and emerging challenges for environmental flows policy, practice and science worldwide. This paper on The Brisbane Declaration and Global Action Agenda on Environmental Flows (2018) describes the inclusive consultation processes that guided the review of the 2007 document. The 2018 Declaration presents an urgent call for action to protect and restore environmental flows and aquatic ecosystems for their biodiversity, intrinsic values and ecosystem services, as a central element of integrated water resources management, and as a foundation for achievement of water-related Sustainable Development Goals. The Global Action Agenda (2018) makes 35 actionable recommendations to guide and support implementation of environmental flows through legislation and regulation, water management programs, and research, linked by partnership arrangements involving diverse stakeholders. An important new element of the Declaration and Action Agenda is the emphasis given to full and equal participation of all cultures, and respect for their rights, responsibilities and systems of governance in environmental water decisions. These social and cultural dimensions of e-flow management warrant far more attention. Actionable recommendations present a pathway forward for a new era of scientific research and innovation, shared visions, collaborative implementation programs and adaptive governance of environmental flows, suited to new social and environmental contexts